Viral myopericarditis masquerading as acute coronary syndrome: Diagnostic role of cardiac MRI - PLN, Kapardhi (Indian Journal of Case Reports, 2024)
Myopericarditis is commonly misdiagnosed as an acute coronary syndrome (ACS) due to the similarities in clinical presentation. Hence, accurate diagnosis is important to ensure appropriate care and improve outcomes. Here, we present the case of a 58-year-old male initially diagnosed with ACS, which was eventually identified to be a case of myopericarditis and managed accordingly. The patient presented with fever for 1 week during the coronavirus disease pandemic and developed signs of ACS subsequently. Clinical history, biomarker profile, and echocardiogram suggested ACS. However, cardiac magnetic resonance imaging and coronary angiography findings revealed myopericarditis and it was managed accordingly. Clinicians should be aware of myopericarditis masquerading as ACS in the post-viral period.